The effects of chitosan-loaded JQ1 nanoparticles on OVCAR-3 cell cycle and apoptosis-related gene expression - Ehsan Masoudi; Mitra Soleimani; Giti Zarinfard; Mansour Homayoun; Mohammad Bakhtiari (Research in Pharmaceutical Sciences, 2024)
Background and purpose: Ovarian cancer is the deadliest gynecological cancer. Bromodomain and extra terminal domain (BET) proteins play major roles in the regulation of gene expression at the epigenetic level. Jun Qi (JQ1) is a potent inhibitor of BET proteins. Regarding the short half-life and poor pharmacokinetic profile, JQ1 was loaded into newly developed nano-carriers. Chitosan nanoparticles are one of the best and potential polymers in cancer treatment. The present study aimed to build chitosan-JQl nanoparticles (Ch-J-NPs), treat OVCAR-3 cells with Ch-J-NPs, and evaluate the effects of these nanoparticles on cell cycle and apoptosis-associated genes. Experimental approach: Ch-J-NPs were synthesized and characterized. The size and morphology of Ch-J-NPs were defined by DLS and FE-SEM techniques. OVCAR-3 cells were cultured and treated with Ch-J-NPs. Then, IC50 was measured using MTT assay. The groups were defined and cells were treated with IC50 concentration of Ch-J-NPs, for 48 h. Finally, cells in different groups were assessed for the expression of genes of interest using quantitative RT-PCR. Findings/Results: IC50 values for Ch-J-NPs were 5.625 μg/mL. RT-PCR results demonstrated that the expression of genes associated with cell cycle activity (c-MYC, hTERT, CDK1, CDK4, and CDK6) was significantly decreased following treatment of cancer cells with Ch-J-NPs. Conversely, the expression of caspase-3, and caspase-9 significantly increased. BAX (pro-apoptotic) to BCL2 (anti-apoptotic) expression ratio, also increased significantly after treatment of cells with Ch-J-NPs. Conclusion and implications: Ch-J-NPs showed significant anti-cell cyclic and apoptotic effects on OVCAR-3 cells.